From Colonization to Domestication : Population, Environment, and the Origins of Agriculture in Eastern North America - Miller, D. Shane (Darcy Shane), 1982- (Book collections on Project MUSE., 2018)
"Winner of the Don D. and Catherine S. Fowler Prize. Eastern North America is one of only a handful of places in the world where people first discovered how to domesticate plants. In this book, anthropologist Shane Miller uses two common, although unconventional, sources of archaeological data, stone tools and the distribution of archaeological sites, to trace subsistence decisions from the initial colonization of the American Southeast at the end of the last Ice Age to the appearance of indigenous domesticated plants roughly 5,000 years ago. Miller argues that the origins of plant domestication lie within the context of a boom/bust cycle that culminated in the mid-Holocene, when hunter-gatherers were able to intensively exploit shellfish, deer, oak, and hickory. After this resource "boom" ended, some groups shifted to other plants in place of oak and hickory, which included the suite of plants that were later domesticated. Accompanying these subsistence trends is evidence for increasing population pressure and declining returns from hunting. Miller contends, however, that the appearance of domesticated plants in eastern North America, rather than simply being an example of necessity as the mother of invention, is the result of individuals adjusting to periods of both abundance and shortfall driven by climate change"--Provided by publisher.